Imperfect Future? Dystopia and Modern Architecture in Stanley Kubrick’ "A Clockwork Orange" - Francisco García Gómez (Anales de Historia del Arte, 2015)
This article tackles with the architectural treatment in the film A Clockwork Orange. Aimed at creating the image of a near future conceived by Burgess in his novel –even though he did not describe it–, Kubrick resorted to the most contemporary design, filming especially in Greater London locations as well as in sets. The outcome is considered to be very modern and became one of the main keys to the visual impact of the film. Thus, we will study its different spaces and analyze the use of modernity by Kubrick.